A proposed sheltered workshop program for the mentally retarded youth in Baguio City - Larioza, Jolly C. 1945- (College of Education, University of the Philippines Diliman, 1977)
This paper described a sheltered workshop program for the mentally-retarded to develop in them certain vocational skills with the ultimate aim of placing these retarded in the local industries and other work-oriented enterprises for gainful living. It also analyzed the objectives, organizational set-up, management, financing, and monitoring of the proposed program. Continuous progress reports of the program must be able to reflect the objectives of the program being aimed at. The program called the sheltered workshop as one that is now recognized by authorities in special education as gainful, profitable, relevant, and humanizing for the mentally-retarded.